Daily students of general schools during the great patriotic war (on the example of the Kabardino-Balkarian Republic) - Alim I. Tetuev (Кавказология, 2023)
For the first time, based on new archival documents and other sources, a reconstruction of the schoolchildren's daily life in wartime conditions was conducted using the example of the Kabardino-Balkarian Republic. This article reveals the influence of a restructuring of the school education system on the daily life of students’ education. The organization of military, physical training and patriotic education of students was analyzed. This work shows the activity of schoolchildren, helping the front, wounded soldiers in evacuated military hospitals, participation in the partisan movement. Forms of helping rears are studied: caring for the families of front-line soldiers, orphans, participating in the restoration of the national economy and agricultural work. The experience of the state work, party bodies and educational institutions in the law’s implementation on universal compulsory education of school-age children is summarized. Problems are analyzed: the introduction of separate education, “Rules for students”, and the quality of students’ knowledge. Difficulties in covering universal education are identified as the main reasons for dropout. It is concluded that the restructuring of the school education system in the interests of the front and rear has significantly affected the daily life of students. Military and physical training, patriotic and labor education of schoolchildren allowed them to help the front and rear and overcome the difficulties of wartime.